2021
DOI: 10.1093/icesjms/fsaa253
|View full text |Cite
|
Sign up to set email alerts
|

Growth rates in a European eel Anguilla anguilla (L., 1758) population show a complex relationship with temperature over a seven-decade otolith biochronology

Abstract: Environmental and habitat change can have profound and complex impacts on fish. We examined an unexploited population of European eel (Anguilla anguilla) from a West of Ireland catchment. The population is long-lived and slow-growing compared to many other European eel populations. Von Bertalanffy growth curves showed decadal changes, with a trend towards larger K, and t0 values in both males and females and a smaller L∞ in females. A growth biochronology spanning seven decades (1950s–2010s) was constructed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…When considering changing migration phenology of eel, there is likely to be some overlap between factors impacting physiological changes associated with the silvering process, and those impacting growth rate across the whole life span of European eel. There is no doubt that growth rates of European Eel are intrinsically linked with water temperature (Daverat et al, 2012;Vaughan et al, 2021), and that as temperatures warm, eels can grow faster and reach maturity at earlier ages. However, this in itself may not impact the timing of the migration, which is primarily determined by the availability of silver eel ready to migrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering changing migration phenology of eel, there is likely to be some overlap between factors impacting physiological changes associated with the silvering process, and those impacting growth rate across the whole life span of European eel. There is no doubt that growth rates of European Eel are intrinsically linked with water temperature (Daverat et al, 2012;Vaughan et al, 2021), and that as temperatures warm, eels can grow faster and reach maturity at earlier ages. However, this in itself may not impact the timing of the migration, which is primarily determined by the availability of silver eel ready to migrate.…”
Section: Discussionmentioning
confidence: 99%
“…As temperatures rise, the glass eel become progressively more pigmented and when temperatures pass 9-11 • C, many commence active migration into freshwaters as elvers. Once in freshwater, elvers grow into yellow eel which is the life stage in which they spend most of their life [7-58 years in the west of Ireland (Poole et al, 2018;Vaughan et al, 2021)]. Eels mature only once when they undergo a process known as silvering before and during their seaward migration.…”
Section: Study Region and Systemmentioning
confidence: 99%
“…A shift towards warmer temperature used is not surprising: both rivers are in the northern part of the species geographic range, where river temperatures are below the temperature optimum for eel growth 41,46 . When comparing silver European eels caught at different latitudes, growth rate tends to increase in the southern regions because of warmer temperatures 41,47 , although it has since been shown that this relationship appears to be more complex 48 . Increasing water temperature due to climate change is expected to increase eel growth in northern regions of Europe 46 , which includes the Imsa and Burrishoole rivers, and expand the geographic range of the European eel northward 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, glass eel/elvers that had only just entered fresh water were sampled, as these would provide individuals whose tissue isotope values would be largely marine based. Larger eels that had already settled in fresh water were also sampled as these would provide individuals whose tissue isotope values would still be in isotopic equilibrium with their diet from the previous summer/autumn periods, given the inactivity of eels in fresh water in cooler temperatures with minimal somatic body growth until water temperatures exceed 16°C (Vaughan et al ., 2021). Thus, the SI relationships between the sampled tissues were considered as reflecting their actual patterns, with minimal influence of recent dietary changes affecting these.…”
Section: Tissue Comparison N Mean Length ± 95% CI (Min Max) (Mm) Tiss...mentioning
confidence: 99%
“…F I G U R E 1 Relationships between lipid normalised δ 13 C (left) and δ 15 N (right) isotope signatures of muscle and mucus (a-b), and fin (c-d) in Anguilla anguilla. Bold lines indicate the line of equality, dashed lines represent the significant relationship of the variables according to linear regression (P < 0.01) and grey shading represents the 95% confidence limits of these linear relationships water temperatures exceed 16 C (Vaughan et al, 2021). Thus, the SI relationships between the sampled tissues were considered as reflecting their actual patterns, with minimal influence of recent dietary changes affecting these.…”
mentioning
confidence: 99%